2011
DOI: 10.1364/boe.3.000075
|View full text |Cite
|
Sign up to set email alerts
|

Optical imaging of metabolism in HER2 overexpressing breast cancer cells

Abstract: The optical redox ratio (fluorescence intensity of NADH divided by that of FAD), was acquired for a panel of breast cancer cell lines to investigate how overexpression of human epidermal growth factor receptor 2 (HER2) affects tumor cell metabolism, and how tumor metabolism may be altered in response to clinically used HER2-targeted therapies. Confocal fluorescence microscopy was used to acquire NADH and FAD auto-fluorescent images. The optical redox ratio was highest in cells overexpressing HER2 and lowest in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
65
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 35 publications
11
65
1
Order By: Relevance
“…Previous studies have shown that OMI endpoints are sensitive to metabolism differences between cancer subtypes [9,13,14]. Additionally, the OMI endpoints provide dynamic readouts of cellular metabolism and detect pre-malignant transformations within tissues [15,16], classify subtypes of breast cancer cells [9,13], and detect response to anti-cancer drugs [14].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that OMI endpoints are sensitive to metabolism differences between cancer subtypes [9,13,14]. Additionally, the OMI endpoints provide dynamic readouts of cellular metabolism and detect pre-malignant transformations within tissues [15,16], classify subtypes of breast cancer cells [9,13], and detect response to anti-cancer drugs [14].…”
Section: Introductionmentioning
confidence: 99%
“…The redox ratio is sensitive to both ER and HER2 overexpression as well as drug response. [11][12][13] NADH and FAD are endogenous fluorophores, and thus enable metabolic measurements without requiring stains or dyes. Therefore, autofluorescence measurements are advantageous for high-throughput drug development.…”
mentioning
confidence: 99%
“…For FAD fluorescence, the cells were excited at 430 to 470 nm and the emission signal was collected at 515 to 555 nm. 12 The instrument was operated under epi-mode with an integration time of 50 μs, a flash frequency of 400 Hz, and a gain of 80. Measurements of each plate were taken twice within ten minutes to rule out the occurrence of photobleaching, and data were collected on three separate days.…”
mentioning
confidence: 99%
“…We have used OMI to study metabolic differences between nontransformed and malignant cells and tissues, the relationship between oncogenic signaling pathways and cellular metabolism, and drug-induced effects on metabolism (18,20,35,37,39). Importantly, our studies demonstrated that OMI is a sensitive and early reporter of drug efficacy in organoids (Fig.…”
Section: Omi As An Early Measure Of Drug Response In Organoidsmentioning
confidence: 83%
“…Fluorescence lifetime studies of cancers have revealed metabolic differences between transformed and premalignant tissues (35,37). OMI can also detect changes in metabolism due to treatment with anticancer drugs (20,35).…”
Section: Omi As An Early Measure Of Drug Response In Organoidsmentioning
confidence: 99%